Application of phase shift masking to sub-micron contact level lithography - Choo, Lay Cheng. (2008)
As device continues to shrink beyond the theoretical limit of the optical exposure tools, other options need to be considered. Resolution Enhancement Techniques (RET), such as Phase Shift Mask (PSM), Optical Proximity Correction (OPC) and / or Off Axis Illumination (OAI) will be required. Various types of PSM have been widely investigated by many lithographers. For contact hole masking, the Attenuated Phase Shift Mask (APSM) is the most feasible option due to the ease in mask fabrication. In addition, the APSM also allows random patterns to be printed.